WWOX somatic ablation in skeletal muscles alters glucose metabolism - Muhannad Abu-Remaileh; Monther Abu-Remaileh; Rania Akkawi; Ibrahim Knani; Shiran Udi; Micheal E. Pacold; Joseph Tam; Rami I. Aqeilan (Elsevier, 2019)
Objective: WWOX, a well-established tumor suppressor, is frequently lost in cancer and plays important roles in DNA damage response and cellular metabolism. Methods: We re-analyzed several genome-wide association studies (GWAS) using the Type 2 Diabetes Knowledge Portal website to uncover WWOX's association with metabolic syndrome (MetS). Using several engineered mouse models, we studied the effect of somatic WWOX loss on glucose homeostasis. Results: Several WWOX variants were found to be strongly associated with MetS disorders. In mouse models, somatic ablation of Wwox in skeletal muscle (WwoxΔSKM) results in weight gain, glucose intolerance, and insulin resistance. Furthermore, WwoxΔSKM mice display reduced amounts of slow-twitch fibers, decreased mitochondrial quantity and activity, and lower glucose oxidation levels. Mechanistically, we found that WWOX physically interacts with the cellular energy sensor AMP-activated protein kinase (AMPK) and that its loss is associated with impaired activation of AMPK, and with significant accumulation of the hypoxia inducible factor 1 alpha (HIF1α) in SKM. Conclusions: Our studies uncover an unforeseen role of the tumor suppressor WWOX in whole-body glucose homeostasis and highlight the intimate relationship between cancer progression and metabolic disorders, particularly obesity and type-2 diabetes. Subject areas: Genetics, Metabolic Syndrome, Diabetes. Keywords: Metabolic syndrome, Tumor suppressor, T2D, WWOX, AMPK